A novel Brassica–rhizotron system to unravel the dynamic changes in root system architecture of oilseed rape under phosphorus deficiency - Yuan, Pan; Ding, Guangda; Cai, Hongmei; Jin, Ke-Mo; Broadley, Martin R.; Xu, Fangsen; Shi, Lei (Oxford Journals, 2016)
Background and Aims: An important adaptation of plants to phosphorus (P) deficiency is to alter root system architecture (RSA) to increase P acquisition from the soil, but soil-based observations of RSA are technically challenging, especially in mature plants. The aim of this study was to investigate the root development and RSA of oilseed rape (Brassica napus L.) under low and high soil P conditions during an entire growth cycle.